Ultrassom de baixa frequência associado à aplicação do óleo de copaiba e melaleuca no processo de cicatrização de úlceras venosas: estudo clínico controlado e randomizado - Caldini, Luana Nunes (2017)
The care with chronic wounds is a function attributed to the nurse, this practice requires knowledge and constant updating of the best therapeutic option and the constant need to know new methods that favors wound healing. Objective: To evaluate the healing process after the application of low-frequency ultrasound associated with copaiba oil and melaleuca without treatment of venous ulcers. Method: This is a randomized controlled clinical trial conducted from October 2016 to July (N = 6 lesions) and the intervention group (n = 6) were randomly assigned to the group of patients with venous ulcers, 8 lesions), with a follow-up of 5 weeks. The control group at the time of standard treatment (dressing with AGE) and the intervention group in the standard treatment associated with the application of low frequency Ultrasound. Instruments were applied to measure as clinical-epidemiological variables and to perform the follow-up recording of the interventions. In addition, photographic recording of the lesions was performed at each intervention, in both groups. After completing the data collection, photographs were compiled and presented to the specialist nurses for evaluation of healing, and they are not informed about which group as lesions were allocated. Data with normal distribution were analyzed using the Student's test and ANOVA for repeated measurements followed by the test and emission data with abnormal distribution, were analyzed by the Mann-Whitney and Friedman test followed by Dunn's post-test. The study was submitted to the evaluation of the Ethics Committee of the involved institutions having an approval based on opinion 1,726,130. Results: In the intervention group, there was a mean area reduction of 2.25 cm² (p <0.05) from the third application, in the control group there was an average area reduction of 2.17 cm² (p <0, 01) from the sixth application. From these averages the size of the intervention effect from D Cohen was 1.35 (strong effect). As well as a strong negative correlation between granulation and fibrin (p <0.001) in the control group and in the intervention group a moderate positive correlation (p <0.001) between the mean area reduction and exudate. Conclusion: The application of ultrasound induces the reduction of the area of the ulcer more quickly when compared to the treatment with AGE, but it also has a strong impact in the reduction of the pain scores from the fifth day (p <0.001). Conclusion: The application of ultrasound induces the reduction of the area of the ulcer faster when compared to the treatment with AGE, but also has a strong impact on the reduction of pain.